Recent advances in traffic engineering for transport networks and systems : 14th Scientific and Technical Conference "Transport Systems. Theory & Practice 2017" selected papers /: 14th Scientific and Technical Conference "Transport Systems. Theory & Practice 2017" selected papers. (©2018) - Unknown
No abstract available